2010
DOI: 10.2174/22102892010010100129
|View full text |Cite
|
Sign up to set email alerts
|

Bradeion Project: Monitoring and Targeting of Cancer: Molecular Marker Diagnosis of Cancer by Fluorescence Correlation Spectroscopy (FCS)

Abstract: The human Sept4/Bradeion GTPase (56Kda) is specifically expressed in colorectal cancer, malignant melanoma, prostate cancer and other urologic cancers such as renal cell carcinoma and bladder cancer. Significance of Bradeion is that, 1) 'all or none' expression, 2) no genetic alterations among patients, and 3) strong tissue-and cell typespecificity. This character satisfies the desired criteria as a target to monitor and control cancer. With the advent of current technology development in nano-scale, we have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Gene fusion AML (Ono et al, 2002;Kadkol et al, 2006;Cerveira et al, 2008) Melanoma (Jaeger et al, 2007) SEPT7 Downregulation Glioma (Nagata et al, 2000;Jiang, 2002;Jiang, 2004;Jia et al, 2010;Tanaka et al, 2010) SEPT8 None None None SEPT9 Amplification/ Breast (Montagna et al, 2003;Scott et al, 2005;overexpression Gonzalez et al, 2007overexpression Gonzalez et al, , 2009) Upregulation Ovary Gene fusion AML, ALL (Strehl et al, 2006;Gulten et al, 2009;Saito et al, 2010) (Santos et al, 2010a,b) (Osaka et al, 1999;Yamamoto et al, 2002;Strehl et al, 2006;Kreuziger et al, 2007) Hypermethylation Colon and head and neck (He et al, 2010;Tierling et al, 2010;Quyun et al, 2010) (Grutzmann et al, 2008;deVos et al, 2009) (Bennett et al, 2008;Lofton-Day et al, 2008;Stanbery et al, 2010) Deletion Ovary, breast Russell et al, 2000) Hodgkin lymphoma (Giefing et al, 2008) SEPT10 None None SEPT11 Gene fusion Deletion AML (Santos et al, 2010b;Stevens et al, 2010) Deletion Liver SEPT12 None None SEPT13 None None SEPT14 None None (Montagna et al, 2003) and the Russell group established that SEPT9 overexpression occurs in various human tumors (Scott et al, 2005). The discovery of DNA hypermethylation at the promoter region of SEPT9 in colorectal (deVos et al, 2009) and head and neck cancer patients (Bennett et al, 2008) complicated the conflicti...…”
Section: Sept6mentioning
confidence: 99%
“…Gene fusion AML (Ono et al, 2002;Kadkol et al, 2006;Cerveira et al, 2008) Melanoma (Jaeger et al, 2007) SEPT7 Downregulation Glioma (Nagata et al, 2000;Jiang, 2002;Jiang, 2004;Jia et al, 2010;Tanaka et al, 2010) SEPT8 None None None SEPT9 Amplification/ Breast (Montagna et al, 2003;Scott et al, 2005;overexpression Gonzalez et al, 2007overexpression Gonzalez et al, , 2009) Upregulation Ovary Gene fusion AML, ALL (Strehl et al, 2006;Gulten et al, 2009;Saito et al, 2010) (Santos et al, 2010a,b) (Osaka et al, 1999;Yamamoto et al, 2002;Strehl et al, 2006;Kreuziger et al, 2007) Hypermethylation Colon and head and neck (He et al, 2010;Tierling et al, 2010;Quyun et al, 2010) (Grutzmann et al, 2008;deVos et al, 2009) (Bennett et al, 2008;Lofton-Day et al, 2008;Stanbery et al, 2010) Deletion Ovary, breast Russell et al, 2000) Hodgkin lymphoma (Giefing et al, 2008) SEPT10 None None SEPT11 Gene fusion Deletion AML (Santos et al, 2010b;Stevens et al, 2010) Deletion Liver SEPT12 None None SEPT13 None None SEPT14 None None (Montagna et al, 2003) and the Russell group established that SEPT9 overexpression occurs in various human tumors (Scott et al, 2005). The discovery of DNA hypermethylation at the promoter region of SEPT9 in colorectal (deVos et al, 2009) and head and neck cancer patients (Bennett et al, 2008) complicated the conflicti...…”
Section: Sept6mentioning
confidence: 99%
“…Using this method, they were able to compare the different expression levels of protein tyrosine kinase‐7 (PTK 7) on human leukemia and HeLa cervical cancer cells. On the other hand, Tanaka et al presented a novel FCS‐based diagnostic technique to detect a cancer biomarker, Sep4/Bradeion GTPase in the serum of patients using monoclonal antibodies. This biomarker is specifically expressed in many types of cancer, such as colorectal, skin, prostate, kidney and bladder cancer and results showed that the method was able to achieve a high diagnostic efficacy of close to 90% for all the various cancer types.…”
Section: Emerging Technologiesmentioning
confidence: 99%